KOHESI DAN KOHERENSI TEKS SANDOSA LAKON SOKRASANA DALAM PENELITIAN KUALITATIF - Endang Retnaningdyah Elis NM. (Institut Seni Indonesia Surakarta, 2013)
Discourse analysis is one of the analytical models which based on the assumption that life with itsentire cultural phenomenon is a text, discourse. Discourse analysis seeks to understand paaroleie. speech, the use of language that can individually be recorded, printed. Parole language isconsidered as an action, and representation mode, and associated with the social structure. Theplay script is a, utterance text that be spoken by a show dalang as the adaptation of the role’scharacters. Parole is the speech of the characters which are interrelated. In a show parole is asocial phenomenon that produce language, as social identity, social relations, and social ideas. Inthe analysis it was performed through several stages of vocabularies, grammar, cohesion, andtext’s structure and architecture. Each text contained form and content. The shape is somethingthat can be sensed, meanwhile the content is the hidden meaning. Each text is always in touchwith form and content.